Sensilla-Specific Expression of Odorant Receptors in the Desert Locust Schistocerca gregaria - Jiang, Xingcong; Breer, Heinz; Pregitzer, Pablo (Frontiers in Physiology, 2019)
The desert locust Schistocerca gregaria recognizes multiple chemical cues, which are received by olfactory sensory neurons housed in morphologically identifiable sensilla. The different sensillum types contain olfactory sensory neurons with different physiological specificities, i.e. they respond to different categories of chemical signals. The molecular basis for the sensilla-specific responsiveness of these cells is unknown, but probably based on the endogenous receptor repertoire. To explore this issue, attempts were made to elucidate whether distinct odorant receptors (ORs) may be expressed in a sensilla-specific manner. Analyzing more than 80 OR types concerning for a sensilla-specific expression revealed that the vast majority was found to be expressed in sensilla basiconica; whereas only three OR types were expressed in sensilla trichodea. Within a sensillum unit, even in the multicellular assembly of sensilla basiconica, many of the OR types were expressed in only a single cell, however, a few OR types were found to be expressed in a consortium of cells typically arranged in a cluster of 2-4 cells. The notion that the OR-specific cell clusters are successively formed in the course of development was confirmed by comparing the expression patterns in different nymph stages. The results of this study uncover some novel and unique features of locust olfactory system, which will contribute to unravel the complexity of locust olfaction.